Development of a tool to measure holistic reflection in midwifery students and midwives. Issue 5 (September 2022) - Bass, J.; Sidebotham, M.; Sweet, L.; Creedy, D.K.
Abstract: Background: Holistic reflection encompasses reflection as a continuum, incorporating critical reflection, reflexivity, critical thinking and a whole-of-person approach. The development of holistic reflection in midwifery students and midwives is rarely measured in a standardised way. Aim: To develop and test a tool to measure holistic reflection in midwifery students and midwives, for use in pre-registration and post-graduate education, and research. Design: The eight-step approach to tool development by DeVellis was followed with psychometric testing of data from a cross-sectional survey. Participants: Midwifery students (pre-registration and postgraduate), and midwifery alumni of an Australian university. Methods: Draft items (n = 84) were generated from review of the literature, qualitative research, and a theoretical model. An expert panel (n = 19) reviewed draft items resulting in 39 items. The survey included demographic details, the draft Holistic Reflection Assessment Tool, emotional intelligence subscale, and a social desirability scale. Participants repeated the online survey at two weeks to confirm test-retest reliability. Results: The 187 responses were received. Exploratory factor analysis with varimax rotation revealed three factors accounting for 49% of variance. Internal consistency of the tool was high ( α  = .91) and test-retest reliability at two weeks ( α  = .93) demonstrated stability. There were low correlations between social desirability (r = .22, p < .001) and emotional intelligence (r = .21, p < .001) with the new holistic reflection scale. Conclusions: The Holistic Reflection Assessment Tool is the first for midwifery. The tool was reliable, stable, and valid. Further research is warranted for criterion validity.